أثر الاتصال الاءداري على الأداء الوظيفي : الثقافة التنظيمية كعامل وسيط دراسة حالة بمكتب وزير الدولة ومحافظ ظفار بسلطنة عمان - Fahad Bakhit Suhail Masan
This study aimed to explore the direct impact of administrative communication on organizational culture and functionality in Office of the Minister of State and Governor of Dhofar in Oman , also aimed to find out the indirect impact of administrative communication on functionality through its impact on organizational culture as a factor mediator. To achieve the objectives of the study default model was developed and it expressed the relationship between the variables of the study, as the administrative communication were considered an independent variable affects the organizational culture as a mediator variable, and the functionality as a dependent variable The researcher designed a questionnaire included 60 items, 346 questionnaires have been distributed to collect data from the study sample, a model study and its hypotheses have been tested using a combination of statistical methods, and that via the Statistical Package program for Social Sciences (SPSS), and the (Smart PLS) program. The study found that there is a direct impact of administrative communication on organizational culture and functionality. And there is in indirect effect of administrative communication on functionality through its impact on organizational culture.